Assessing the willingness of rural homeowners to insure their homes in South Africa using multilevel modelling - Skenjana, Samkele (University of the Free State, 2023)
There has been an increase in urbanisation in the last decade as more South African seeks better work opportunities in the urban areas. Despite this notable increase, there are individuals who still prefer to build houses and reside in rural areas. There are reasons why people in South Africa have opted to invest in properties in rural areas. Firstly, the process to obtain land in rural areas is through a traditional leader or chief of the village (much easier than in the urban areas). Secondly, the cost of the land in the rural areas is significantly lower than the cost of land in the urban areas. As valid as these reasons are, they have drawbacks such as owners of the not having a title deed for their land and an accurate amount of the value of their land. This makes it difficult to insure these homes. The absence of a rural home insurance in South Africa that focuses on these rural homeowners fitting the description above was the driving force behind the need for this study. Literature thus far has been focused on agricultural and crop insurance in rural areas. This study will explore the challenges in the rural insurance market in South Africa and factors affecting the willingness of these rural residents to insure their rural homes.
Dissertation (M.Sc.(Actuarial Science))--University of the Free State, 2023
Keywords: Short-term insurance; Rural home insurance; Multilevel modelling; Urbanisation; Rural homeowners